2009
DOI: 10.1177/1403494809344653
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of Common Mental Disorders — Screening Questionnaire (CMD-SQ) in long-term sickness absence

Abstract: SCL-8AD, a sub-scale of CMD-SQ, is a promising candidate for screening and measurement of mental disorders in long-term sickness absence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
(41 reference statements)
0
19
0
1
Order By: Relevance
“…Successful ageing (SA) was operationalized as a latent construct composed of three dimensions: (1) mental health, (2) social (dis)connectedness, and (3) life satisfaction. Mental health facet was indicated by a brief and psychometrically validated depression scale, the Symptom Checklist Depression (SCL-DEP; Søgaard & Bech, 2009). The 6-item scale had acceptable reliability in this study (country-specific Cronbach's was in the .79-.83 range).…”
Section: Methodsmentioning
confidence: 99%
“…Successful ageing (SA) was operationalized as a latent construct composed of three dimensions: (1) mental health, (2) social (dis)connectedness, and (3) life satisfaction. Mental health facet was indicated by a brief and psychometrically validated depression scale, the Symptom Checklist Depression (SCL-DEP; Søgaard & Bech, 2009). The 6-item scale had acceptable reliability in this study (country-specific Cronbach's was in the .79-.83 range).…”
Section: Methodsmentioning
confidence: 99%
“…This method has been validated in previous studies where it showed to be comparable with a semi-structured psychiatric interview [32, 33]. …”
Section: Methodsmentioning
confidence: 99%
“…[15][16]. This has been established as a subscale of the total SCL and has been utilized in Danish and Swedish population studies.…”
Section: Methodsmentioning
confidence: 99%